The frequency of non-motor symptoms in SCA3 and their association with disease severity and lifestyle factors - Hengel, Holger (2023)
Background Non-motor symptoms (NMS) are a substantial burden for patients with SCA3. There are limited data on their frequency, and their relation with disease severity and activities of daily living is not clear. In addition, lifestyle may either influence or be affected by the occurrence of NMS. Objective To characterize NMS in SCA3 and investigate possible associations with disease severity and lifestyle factors. Methods In a prospective cohort study, we performed a cross-sectional analysis of NMS in 227 SCA3 patients, 42 pre-ataxic mutation carriers, and 112 controls and tested for associations with SARA score, activities of daily living, and the lifestyle factors alcohol consumption, smoking and physical activity. Results Sleep disturbance, restless legs syndrome, mild cognitive impairment, depression, bladder dysfunction and pallhypesthesia were frequent among SCA3 patients, while mainly absent in pre-ataxic mutation carriers. Except for restless legs syndrome, NMS correlated significantly with disease severity and activities of daily living. Alcohol abstinence was associated with bladder dysfunction. Patients with higher physical activity showed less cognitive impairment and fewer depressive symptoms, but these differences were not significant. Conclusion This study revealed a clear association between disease severity and NMS, likely driven by the progression of the widespread neurodegenerative process. Associations between lifestyle and NMS can probably be attributed to the influence of NMS on lifestyle.